the THE CORRELATION BETWEEN SELF-EFFICACY OF POOR MOTHER WITH NUTRITIONAL PATTERN TO UNDER-FIVE CHILDREN - Tri Ratna Ningsih; Moh Ali mansur; arif efendi (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Nutrition fulfill was an important thing to be considered in increasing the nutrition status of under-fives, because under five years old children had rapid growth phase. Therefore, the intake of nutrition need to get more attention. The purpose of this research was to analyze the correlation between self-efficacy of mother from poor families with nutritional parenting pattern of under-fives in the area of Mojokerto Regency East Java. The research design used case control with case population which was poor mother with healthy under-fives and control population was poor mother with under-fives who had nutritional problems. The number of sample was 79 people for case group and 41 people for control group. The sampling technique used multi stage sampling. The data collection used questionnaire which had beed tested the validity and reliability to 30 people. The data analysis used statistic chi square test. The research result showed that the correlation of self-efficacy with good parenting pattern as many as 68 people (81,0%) the analysis result with chi square obtained uji p = 0,000, self-efficacy with good love pattern as many as 52 people (61,9 %) the result analysis with chi square test obtained p = 0,000, self-efficacy with sharpening pattern as many as 57 people (67,9%) the analysis result of chi square test obtained p = 0,000, self-efficacy with nutritional parenting pattern as many as 44 people (52,4%) the result of analysis with chi square test obtained p = 0.001, value of Î± = 0,05, meant there was correlation between self-efficacy with nutritional parenting pattern of under-fives. The nutritional parenting of under-fives was important to be considered because it had huge impact and prolonged impact on health status, physic and mental development, and also the productivity of children when they grew up, so self-efficacy was needed to give nutrition to their under-fives.